Tissue distribution of sulphadimidine sodium in non-starved and starved grower turkeys (meleagris gallopavo) - Agbo, Joseph; Saganuwan, Alhaji Saganuwan; Azubuike, Patrick (International Journal of Pharmacology and Toxicology, 2016)
Background: The use of veterinary drugs in food-producing animals has potential to generate residues in edible tissues and posses health hazard to consumers especially when the withdrawal period is not observed.Objectives: The study was conducted to determine the tissue residue and withdrawal period of sulphadimidine in non-starved and starved grower turkeys following a single intramuscular administration.Methods: Forty two turkeys of both sexes and 12 weeks old weighing 1.57Â±0.2 kg were divided into two groups of twenty one each. One group was administered a single intramuscular dose of sulphadimidine sodium (100mg/kg body weight). The other group was kept off-feed for 48 hours before drug administration. Three turkeys each were sacrificed from the starved and non-starved group and two grammes (2g) of tissue sample were harvested from selected tissues.Results: The results showed that the drug residues persisted in all the tissues of turkeys sampled for up to thirty (30) days after drug administration. The starved turkeys maintained consistently higher concentrations of the drug in the tissues than fed ones. Sulphadimidine residue was significantly increased (p<0.05) between days 3 to 6 in the spleen of non-starved turkeys. However, the concentrations in the spleen decreased significantly (p<0.05) between days 6 to 10 and 25 to 30.Conclusion: Sulphadimidine residue persisted in the tissues of non-starved and starved turkeys for up to 30 days after intramuscular injection. This should be given due consideration in the estimation of the withdrawal period for the drug, since sulphadimidine residue in meat > 0.2 ppm is unsafe for human consumption.